2014
DOI: 10.1242/dev.097022
|View full text |Cite
|
Sign up to set email alerts
|

Endophilin B is required for the Drosophila oocyte to endocytose yolk downstream of Oskar

Abstract: The nutritional environment is crucial for Drosophila oogenesis in terms of controlling hormonal conditions that regulate yolk production and the progress of vitellogenesis. Here, we discovered that Drosophila Endophilin B (D-EndoB), a member of the endophilin family, is required for yolk endocytosis as it regulates membrane dynamics in developing egg chambers. Loss of D-EndoB leads to yolk content reduction, similar to that seen in yolkless mutants, and also causes poor fecundity. In addition, mutant egg cham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Both Short and Long Oskar localize at the posterior pole of oocytes. However, while Short Oskar localizes, together with Vasa, to electrondense particles termed polar granules, Long Oskar is excluded from these structures and instead localizes to endocytic membranes along the oocyte cortex (Breitwieser et al 1996;Mahowald 1962;Tsai et al 2014;Vanzo et al 2007). Unlike Short Oskar, Long Oskar is not present in pole cells (Markussen et al 1995).…”
Section: Oskar -The Drosophila Germ Plasm Organizermentioning
confidence: 99%
“…Both Short and Long Oskar localize at the posterior pole of oocytes. However, while Short Oskar localizes, together with Vasa, to electrondense particles termed polar granules, Long Oskar is excluded from these structures and instead localizes to endocytic membranes along the oocyte cortex (Breitwieser et al 1996;Mahowald 1962;Tsai et al 2014;Vanzo et al 2007). Unlike Short Oskar, Long Oskar is not present in pole cells (Markussen et al 1995).…”
Section: Oskar -The Drosophila Germ Plasm Organizermentioning
confidence: 99%
“…Loss of EndoA has been shown to cause severe endocytic defects and impair neurotransmission in various models (Verstreken et al ., 2002 ; Milosevic et al ., 2011 ). Endophilin B (D‐EndoB) is required for yolk endocytosis in Drosophila melanogaster ; loss of D‐EndoB reduces yolk content similar to yolkless mutants and results in low female fertility (Tsai et al ., 2014 ). However, it is unclear whether EndoA is involved in yolk endocytosis during oogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we found that RNAi-mediated deletion of Endophilin B1 resulted in underdeveloped ovaries, and decreased fecundity, which is consistent with the results that showed that endophilin B could regulate progression of vitellogenesis in Drosophila. 67 However, injection of miR-311-3p agomir had no effect on the expression of Vg in the fat body at the transcriptional level, possibly as a result of the high expression of the miR-311-3p in the ovary and primary involvement in the uptake of yolk by receptor-mediated endocytosis, thus controlling ovarian development and fertility. The abundance of yolk protein in the hemolymph needs to be measured in a further study.…”
Section: Discussionmentioning
confidence: 98%
“…Drosophila Endophilin B acts in Oskar-induced endocytosis that facilitates yolk protein deposition into the oocyte and acceleration of vitellogenesis and thus improves fecundity. 67,68 Indeed, the expression level of Endophilin B was positively correlated with egg production in Drosophila; a high level of Endophilin B resulted in a 30% increase in fecundity by promoting endocytosis in the oocyte. 65 However, miRNAs that target Endophilin B to regulate reproduction have not been identified in Drosophila.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation